The Effects of 6-Month Exclusive Breastfeeding on Febrile Seizure: A Systematic Review and Meta-Analysis - vard, bahareh; Yazdi, Maryam; Akbarzadeh, Zahra; Rouzbahani , Shiva; Kelishadi, Roya (Iranian Journal of Child Neurology, 2025)
Objectives: Prior research investigating the variance in febrile seizure (FS) incidence between 6-month-old exclusively breastfed (EBF) and partially breastfed children has yielded inconsistent findings. To fill this void, this study conducted a systematic review and meta-analysis. Materials & Methods: This study performed a search across electronic databases, including PubMed, Scopus, the Cochrane Library, and Google Scholar without any restrictions, from the year 2000 up to January 2024. Results: Thirteen studies were reviewed. Regarding six articles (data number=1876753) used in the meta-analysis, EBF (OR=0.65, 95% CI: 0.50, 0.85) and partial breastfeeding (OR=0.92, 96% CI: 0.91, 94) were both significantly associated with lower risks of FS. However, the association in the EBF group was stronger. Conclusion: Breastfeeding positively affects lowering the risk of FS. Encouraging mothers to breastfeed and implementing preventive strategies can be beneficial for health policymakers in reducing the incidence of FS.